Blackness at the End of the World - Antavius Franklin (Black Theology Papers Project)
This paper argues that there exists no ontotheological grounds for black life. As such, black religion and, by extension, black theology should consider the ways in which black life is life that is lived ungrounded. The central claim of this paper notes that categories such as the good life, the human, freedom, and citizenship are inadequate to account for the reality of black life amid the totalizing effects of antiblackness. As such, black theology should position itself to imagine black theology beyond the confines of the science of faith and other colonial markers of life and humanity. In essence, this paper seeks to make two theological claims/interventions; first, it questions the use of the category of the human as a liberatory figure through which the black can attain freedom. Second, it throws into crisis the notion of eschatological time and salvation and the inability or difficulty to account for the black who has been rendered simultaneously in and out of time. Ultimately, this paper wants to think with black feminist futurity and Afrofuturist discourse as generative tools to imagine black life beyond the confines of antiblackness, if at all possible.